A Tale of Two Countries : Labor Market Profiles of Youth in Urban and Rural Cameroon - Botea, Ioana; Del Bono, Mitja (World Bank, Washington, DC, 2022)
Cameroon’s high employment levels mask widespread precariousness and rural-urban inequality. Labor market vulnerability-either detachment or weak attachment-is particularly acute among youth (ages 15 to 35), who are often uninterested in agriculture yet unable to access better opportunities in urban areas. Using Latent Class Analysis (LCA), a non-parametric method that segments a heterogeneous population into groups sharing similar characteristics, we identify distinct profiles of youth experiencing labor market vulnerability. The largest groups in urban and rural areas consist of mostly men with some education who work full time in the informal sector, either as own-account workers or subsistence farmers. In addition, we identify five groups as priorities for policy intervention. First, two groups making up 9 percent of out-of-school youth, predominantly married women, are involuntarily inactive and present an opportunity for improved human capital utilization. Second, a third group (14 percent) includes women in rural areas employed as contributing family workers, while two other groups (12 percent) comprise women facing multifold vulnerabilities (i.e., a combination of unpaid, temporary, and part-time work). Tailored interventions for these three groups would most impact poverty reduction